APLIKASI PARKIR KENDARAAN RODA DUA BERBASIS WEB (STUDI KASUS : STMIK NURDIN HAMZAH JAMBI): PROCESSING SYSTEM VEHICLE PARKING, PHP, BOOTSTRAP, FRAMEWORK CODEIGNITER, UML, USE CASE, ACTIVITY DIAGRAM - Lisdarti (LP2M STMIK Nurdin Hamzah Jambi, 2017)
The parking process at STMIK NH Jambi is still done manually which is only supervised by the security guard on duty at that time, so there is still a weakness in terms of security where the security guard can not control the vehicle in and out during the hours of duty. The purpose of this study is to create a web-based program, especially to facilitate the management of two-wheel parking, data collection and supervision, using the programming language PHP, Bootstrap¸framework CodeIgniter, and PHP Myadmin as a database. The methodology used in this study is directed object, which is poured using UML (Unified Modeling Language) that is Use Case Diagram, Activity Diagram, and Class Diagram and designing data structure. The results of this parking application processing application is expected to provide ease and safety in the parking process. It can be concluded that this vehicle parking processing application can assist in the issue of incoming and outgoing vehicle governance in detail with clear reports.